Utilization Of Waste From Vco Production As A Nata De Coco Stater ToIncrease The Income Of The People Of Kwt “Bengke Sakato”.: Pemanfaatan Limbah Pembuatan VCO Menjadi Stater Nata De CocoUntuk Meningkatkan Pendapatan Masyarakat KWT”Bengke Sakato” - Suryani, Suryani; Helga Yermadona; Nurhaida Nurhaida; Adelia Pramita Sari; Yunita Sabri; Rahmawati Rahmawati; Femi Earnestly (KPN Kopertis X, 2022)
The service partner of KWT